Experience in adapting the “Undergraduate Stress Questionnaire” (The Journal of Psychology and Sociology, 2021)
This article describes the process of adapting the “Undergraduate Stress Questionnaire (USQ)” ques- tionnaire for a Russian-speaking sample of Kazakhstani students. The questionnaire is aimed at studying various parameters of academic stress and describes stressful events associated with both the education- al process and the extracurricular life of students. The aim of the study is translation, cultural adaptation and verification of psychometric properties of the adapted version of the questionnaire. The results of the study revealed that the Russian-language version of the questionnaire has good psychometric data. The internal consistency coefficient of α-Cronbach is 0.929. A statistically significant correlation was found between the adapted questionnaire and the diagnostic tools used to test the convergent validity (the correlation coefficients range from 0.438 to 0.836). Satisfactory indicators of retest reliability of the questionnaire were obtained (r = 0.889). These data are consistent with the results obtained by the authors of the original questionnaire. The Russian-language version of the Undergraduate Stress Ques- tionnaire, called the Student Stress Questionnaire, can be used to study the quantitative and qualitative characteristics of academic stress in the context of Kazakhstan.Key words: questionnaire, adaptation, academic stress, diagnostics.